Failure of fresh frozen plasma infusion and vitamin K to correct elevated international normalised ratio. (16th July 2012) - Vitish-Sharma, P; Shah, R; Anjari, M; Knowles, J; Qurashi, K
Abstract : An 83-year-old, otherwise well, Caucasian gentleman was admitted with an incarcerated inguinal hernia. Routine preoperative tests revealed a raised international normalised ratio of 7.4, prothrombin time of 72.1 s and activated partial thromboplastin time of 73.1 s with normal liver and renal function tests. Despite fresh frozen plasma 15 ml/kg, and vitamin K, his repeat clotting remained deranged. The patient went on to have his hernia repair, and intraoperative bleeding remained normal despite the deranged clotting. The presence of endogenous clotting inhibitors can cause deranged coagulation studies but not impair bleeding. As in this case, the patient underwent surgery with no abnormal bleeding.